Pelatihan Pembuatan Pupuk Organik Cair dari Limbah Ternak Sapi - Siti Nurhidayati; Khaeruman Khaeruman; Maulida Rahmi (Nuras : Jurnal Pengabdian Kepada Masyarakat, 2024)
The training on the production of liquid organic fertilizer from cattle waste in Merembu Village, Labuapi Subdistrict, West Lombok Regency aimed to enhance the participants' knowledge and skills in managing livestock waste into economically valuable and environmentally friendly products. This training utilized Participatory Rapid Appraisal (PRA) and Participatory Learning and Action (PLA) methods, engaging participants actively at every stage of the learning process. Results from pre- and post-training questionnaires showed a significant increase in participants' knowledge and understanding, with an average score improvement of 55%. Observations and document studies indicated that participants successfully applied correct fermentation techniques and improved waste management methods. Additionally, some participants achieved halal certification, positively impacting their product operations and marketing. Case studies and literature demonstrate that processing cattle waste into liquid organic fertilizer can enhance soil fertility and crop yields, while reducing environmental pollution and greenhouse gas emissions. The training not only provided economic benefits by opening new business opportunities but also raised environmental awareness among participants, fostering a more caring and proactive community in maintaining environmental cleanliness and health.